THE IMPACT OF FUEL PRICE INCREASE ON STOCK PRICE IN INDONESIA STOCK EXCHANGE - Teddy Chandra (Journal of Economics, Business, and Accountancy Ventura, 2013)
The purpose of this research is to analyze the response ofIndonesian Capital Market to increase in fuel price as announced by the Government on June 22nd, 2013. This study uses abnormal returns and trading volume activity as the indicatorsto observe investors’ responses in the capital market. Event study is used in order to examine investors’ responses. It measures the investors’ response before and after the announcement of increase infuel price. The sample used in this study includes all companies listed on the LQ-45 for the period of February to July 2013. The result indicates that there are significant negative abnormal returns before the announcement of increasing in fuel price and there are positive abnormal returns after the announcement of increasing in fuel price. However,there is no significant difference between the abnormal returns before and after the announcement. Additionally, there is an increase in activity shown by the increase in trading volume activity before and after the announcement. Yet, there is no significant difference between the activity before and after the announcement.